Nitrogen scheduling for improving productivity and quality of durum wheat (Triticum turgidum) in central India - Behera, U K; Saiprasad, S V; Pradhan, S (The Indian Journal of Agricultural Sciences, 2008)
Field experiments were conducted in Vertisols having clay loam texture at the research farm of Regional Station, Indian Agricultural Research Institute, Indore during 1999-2002 to evaluate the yield performance, nitrogen-use efficiency and quality parameters of durum wheat (Triticum turgidum var. durum Desf.) under different N management practices. Grain yield and quality parameters of wheat were significantly influenced under recommended N application over 50% N and control. Contrary to recommended practice of applying N in 2 splits, the basal application of entire dose of N gave the highest grain yield and net returns. However, 2 splits (25% basal + 75% at crown-root initiation or first node) or 3 splits (25% basal + 50% at first node + 25% at late jointing) resulted in maximum protein (11.07%) and minimum yellow berry content (11.7%) in grain. Neem (Azadirachta indica A. Juss L.)-coated urea did not show superiority to prilled urea. The results showed that the profitability can be enhanced by applying full nitrogen as basal but for better grain quality split application should be done for growing durum wheat in central India in black soils.